An Anatomic Reconstruction of Both the Anterior Cruciate Ligament and Fibular Collateral Ligament Using Autografts - Luke V. Tollefson, B.S.; Evan P. Shoemaker, B.A.; Nathan J. Jacobson, M.D.; Erik L. Slette, M.D.; Robert F. LaPrade, M.D., Ph.D. (Arthroscopy Techniques)
Fibular collateral ligament (FCL) tears rarely occur in isolation and are typically injured in conjunction with another ligament, including the anterior cruciate ligament (ACL). Reconstruction of both ACL and the FCL is critical to restore proper knee biomechanics and stability. This technique describes an anatomic reconstruction of both the ACL using a bone–patellar tendon–bone autograft and the FCL using a semitendinosus hamstring autograft. Previous biomechanical studies have reported on the effect of ACL and FCL tears on lateral gapping and the importance of reconstruction to restore near native stability. Outcomes studies have reported positive patient outcomes for both techniques individually and together.